Meet the Prophets: A Beginner's Guide to the Books of the Biblical Prophets - Miller J. W. (New Jersey Mahwah Paulist Press, 1987)
Meet the Prophets is a carefully organized, clear and up-to-date introductory text to the books of the biblical prophets, with a special focus on seven of the most omportant of these writing. Author John W. Miller thoroughly presents the books as a whole, the men behind them, their messages, and the relevance of these messages then and now.
Keywords: 27 (NhRISTIQNSTWOs